The respectability of late Victorian workers : a case study of York, 1867-1914 - Masters, Charles Walter (Cambridge Scholars, 2010)
This study of the working classes of York in the late Victorian period places respectability at the heart of the interpretation of working-class culture, drawing attention to its distinctive role within working-class daily life while eschewing a class-bas.